P62 'REVIVING, SURVIVING, THRIVING': Assessing the impact of in-situ simulation on response to deteriorating patients. (3rd November 2019) - Cyril, Sindhu; Bui, Anh; Donaldson, Ian; Dimmock, Valerie
Abstract : Introduction: Ensuring that patients who deteriorate receive appropriate and timely care is a key safety and quality challenge and a national priority. All patients should receive comprehensive care regardless of their location in the hospital or the time of day. Nurses who have the most frequent patient contact and responsibility for ongoing monitoring of patients play a crucial role in recognising and responding to clinical deterioration. The importance of education in supporting nurses to enhance their Acute Care Skills (ACS) and improve management of deteriorating patients is paramount. Methods: Explore the educational strategies to ensure qualified nurses are competent to accurately assess patients and recognise clinical deterioration; appreciate the urgency of a situation; can communicate effectively to escalate care and provide immediate appropriate interventions. Design: Phase 1: Tailored, classroom based teaching session for all nurses on ACS Study Day followed by an Objective Structured Clinical Examination to assess competencies. Facilitated learning and implementation of the National Early Warning Score (NEWS) 2. Phase 2: In-situ simulation focusing on deteriorating patients, human factors, situation awareness, structured communication and detection of latent errors. Feedback post teaching sessions and simulation for educational improvement. Preliminary results: Post phase 1, Identified that nurses have adequate theoretical knowledge but fail to respond to deterioration in a consistent and timely manner as evidenced by clinical documentation. Post phase 2, Clinical response and review, speed of response and seniority review were measured and remained the same between September 2018 and December 2018 (data collection): From January 2019, monthly ward based in-situ simulation program are planned and feedback will be collected quantitatively and qualitatively. Conclusion: The educational strategies have highlighted important aspects of patient safety in clinical deterioration and the role of qualified nurses. The program has assisted nurses to have the knowledge and skills needed to recognise and respond to patient deterioration in a more timely and effective way. These strategies include: utilising clinical decision-making models; developing a standardised tool for systematic nursing assessment and management of clinical deterioration and conducting more rigorous studies to evaluate the effectiveness of the educational programs. Results to be presented at conference.